Baji Rao: The Warrior Peshwa - Paul, E. Jaiwant (New Delhi Rolli Books, 2003)
Peshwa Baji Rao, the great Maratha general and statesman, changed the map of India in the mid-eighteenth century. His military campaigns were classic examples of his genius. In the mayhem of the religious intolerance continued by the tottering Mughals after Aurangzeb, Baji Rao stood out as the champion of Hinduism.
Keywords: History